NANO STRUCTURE AND MAGNETIC PROPERTIES OF Zn FERRITE AND ZnCuNi FERRITE USING THE Co-PRECIPITATION METHOD - SAGALA, LIDIA PUSPITA SARI (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2023)
AbstractZn Ferrite and ZnCuNi Ferrite with a composition of ZnFe2O4 and Zn0.9Cu0.05Ni0.05 Fe2O4 have been synthesis using the co-precipitation method. Zn Ferrite and ZnCuNi Ferrite have been synthesized at 100 oC. Structure, morphology and magnetic properties were obtained by the characterization of  X-ray Difraction (XRD), Field Emission-Scanning Electron Microscope (FE-SEM) and Vibrating Sample Magnetometer (VSM). The X-Ray Diffraction (XRD) characterization showed the cubic spinel structure of Zn Ferrite and ZnCuNi Ferrite. The microstructure and magnetic properties have been changed with the addition of Cu2+ and Ni2+ to ZnFe2O4. The grain size increased from 13.4098 nm to 13.7184 nm. The VSM test results also showed an increase in saturation mangetization from 14.76 emu/g to 26.67 emu/g. Meanwhile, the magnetic coercivity value experienced the opposite, which decreased from 87.85 Oe to 87.65 Oe. The addition of Cu2+ and Ni2+ increases the magnetization of the spinel ferrite and decreases its magnetic coercivity.  Keywords: FE-SEM; Magnetic Properties; Microstructure; VSM; XRDAbstrakZn ferit dan ZnCuNi ferit dengan komposisi ZnFe2O4 dan Zn0.9Cu0.05Ni0.05Fe2O4 masing-masing telah disintesis dengan menggunakan metode kopresipitasi. Zn ferit dan ZnCuNi ferit tersebut telah disintesis pada suhu 100 oC. Struktur, morfologi dan sifat kemagnetannya diperoleh dari karakterisasi X-ray Diffraction (XRD), Field Emission – Scanning Electron Microscope (FE-SEM) dan Vibrating Sample Magnetometer (VSM). Karakterisasi X-ray Diffraction (XRD) menunjukkan struktur spinel kubik pada Zn ferit dan ZnCuNi ferit.  Mikrostruktur dan sifat magnetik mengalami perubahan dengan adanya penambahan Cu2+ dan Ni2+ pada ZnFe2O4. Ukuran butir meningkat dari 13,409 nm menjadi 13,718 nm. Dari hasil uji VSM juga menunjukkan adanya peningkatan mangetisasi saturasi dari 14,76 emu/g menjadi 26,67 emu/g. Sementara nilai koersivitas magnet mengalami sebaliknya, yaitu menurun dari 87,85 Oe menjadi 87,65 Oe. Penambahan Cu2+ dan Ni2+ meningkatkan magnetisasi spinel ferit dan menurunkan nilai koersivitas magnetnya.  Kata kunci : FE-SEM; Sifat Magnetik; Mikrostruktur; VSM; XRD